2004
DOI: 10.1139/f04-123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay turbidity and light on the predator–prey interaction between smelts and chaoborids

Abstract: The effects of clay turbidity and light on the predator–prey interaction between planktivorous smelts (Osmerus eperlanus) and phantom midge (Chaoborus flavicans) larvae were studied by means of laboratory experiments. Irrespective of light intensity, fish-mediated mortality of chaoborid larvae was highest at intermediate turbidity (20 nephelometric turbidity units (NTU)). Increases in light intensity enhanced the feeding rate of smelts at very low light intensities. A regression model describing the dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 31 publications
7
82
0
1
Order By: Relevance
“…Foraging of most planktivorous fish is directed by vision (Lazzaro, 1987), thus that factor can determine the abundance of some aquatic communities, especially crustaceans (Estlander et al, 2009). Planktonic crustaceans can be protected against predation by water turbidity, for suspended particles severely disturb prey detection by fish due to their effects on light scattering (Horppila et al, 2004). Because water transparency is important in order for crustaceans to avoid predators, it has less importance for their foraging since cladocerans forage unselectively (Burns, 1968), and copepods use mechanoreceptors to detect their prey (Williamson, 1986) and chemoreceptors to capture the most nutritional particles (Paffenho¨fer and Van Sant, 1985).…”
Section: Contribution Of Environmental Factors To Food Web Relationsmentioning
confidence: 99%
“…Foraging of most planktivorous fish is directed by vision (Lazzaro, 1987), thus that factor can determine the abundance of some aquatic communities, especially crustaceans (Estlander et al, 2009). Planktonic crustaceans can be protected against predation by water turbidity, for suspended particles severely disturb prey detection by fish due to their effects on light scattering (Horppila et al, 2004). Because water transparency is important in order for crustaceans to avoid predators, it has less importance for their foraging since cladocerans forage unselectively (Burns, 1968), and copepods use mechanoreceptors to detect their prey (Williamson, 1986) and chemoreceptors to capture the most nutritional particles (Paffenho¨fer and Van Sant, 1985).…”
Section: Contribution Of Environmental Factors To Food Web Relationsmentioning
confidence: 99%
“…They dominated particularly at the deeper sites (6, 7), but were also abundant in the rest of the study area. Since these animals are selectively taken by fish (Horppila&Liljendahl-Nurminen 2005), they are usually highly abundant in fishless water bodies (Xie et al 1998) or when suitable shelters are present in the environment (Horppila et al 2004). In deeper, stratified lakes, particularly eutrophic ones, they migrate down to the dark, poorly oxygenated hypolimnion (Hanazato 1992, Horppila&Liljendahl-Nurminen 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its effects on light scattering, high turbidity severely impaim prey detection by fish (Vinyard and O'Brien 1976, Horppila et al 2004) and can therefore protect prey animals even in shallow waten where very low light intensities may not be found Some studies have indicated that the importance of structural plant complexity as a refige may decrease with increasing turbidity (Snickars et al 2004). If predators are present among littoral vegetation and water quality outside the macrophyte stands is not favorable for visual @tion, prey animals may prefer the open water area instead of littoral vegetation zone even during daytime.…”
Section: Introductionmentioning
confidence: 99%